Pelatihan Pembuatan Pupuk Asam Amino Pengganti NPK Bagi Gapoktan di Desa Kedungrejo - Zulfah, Machnunah Ani; Ashlihah, Ashlihah; Ro'aini, Lilis; Al Alawiyi, Moch. Amiruddiin; Al-Hadi, Muhammad Ubaidillah; Wijaya, Sundy (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2024)
The agricultural sector is the economic basis of the people of Kedungrejo Village, so there are many problems in the agricultural sector in Kedungrejo Village. One of the problems being faced is the use of inorganic fertilizers. Most farmers use inorganic fertilizers to increase crop production in a short time. However, if used intensively, the use of inorganic fertilizers or chemical fertilizers will have a negative impact on soil fertility, soil pollution and can even lead to water pollution. For this reason, in dealing with this problem, it is highly recommended that organic fertilizer be applied so that the soil remains fertile. Utilization of processed fish waste to make useful new products. One effort to utilize this waste is to make it into environmentally friendly liquid organic fertilizer. The PKM activity of using fish waste as liquid organic fertilizer aims to provide information and understanding to farmers about amino acid fertilizer from fish waste. Benefits and also how to make it. So the target of this PKM activity is a group leading to a productive economy, namely GAPOKTAN Kedungrejo Village. The approach or method used by researchers is Service Learning (SL). During the implementation, namely training in making liquid organic fertilizer from fish waste at the Association of Farmers' Groups (GAPOKTAN) in Kedungrejo Village, they understood the benefits and use of liquid organic fertilizer from fish waste. Kedungrejo Village farmers already know how to make liquid organic fertilizer from fish waste with assistance from Wahab Hasbullah University students. In terms of other sectors, the products produced by the Association of Farmer Groups (GAPOKTAN) can be developed into large-scale manufacturing for packaging and sale to the public.